Abzan: a prudent remedy for a plethora of medical ailments - Wani, Nasir Nazir; Ashraf, Aaqib; Wani, Khalid Rahim; Hamid, Shugufta; Jalal, Barjes (International Journal Of Community Medicine And Public Health, 2025)
In the Unāni system of medicine, there are three methods of treatment viz; ilaj-bit-tadbeer wa ghiza (regimenal therapy and dietotherapy), ilaj- bil- dawa (pharmacotherapy) and ilaj- bil- yad (Surgery). Ilaj-bit-tadbeer is one of the most popular treatments practiced by ancient Unāni physicians for ages. Ābzan (Sitz bath) is one of the procedures of ilaj-bit-tadbeer described in the Unani system of medicine used to manage various diseases. Ābzan (sitz bath) is a type of bath in which hips and buttocks are immersed in water, either plain or medicated (Joshanda, Khaisanda), for therapeutic effects. This article aims to discuss and clarify several aspects of Ābzan, including its clinical applications in Unāni medicine. However, for rational demonstration of the effectiveness of Ābzan in the modern period, standard operating procedures (SOP) and scientific standards must be developed. Unāni system of medicine is enriched with the concept of Ābzan. To benefit the community, more research should be done to explore the efficacy of Ābzan in managing diseases.